Geomagnetically induced currents: Science, engineering, and applications readiness. Issue 7 (6th July 2017) - Pulkkinen, A.; Bernabeu, E.; Thomson, A.; Viljanen, A.; Pirjola, R.; Boteler, D.; Eichner, J.; Cilliers, P. J.; Welling, D.; Savani, N. P.; Weigel, R. S.; Love, J. J.; et al.
Abstract: This paper is the primary deliverable of the very first NASA Living With a Star Institute Working Group, Geomagnetically Induced Currents (GIC) Working Group. The paper provides a broad overview of the current status and future challenges pertaining to the science, engineering, and applications of the GIC problem. Science is understood here as the basic space and Earth sciences research that allows improved understanding and physics‐based modeling of the physical processes behind GIC. Engineering, in turn, is understood here as the "impact" aspect of GIC. Applications are understood as the models, tools, and activities that can provide actionable information to entities such as power systems operators for mitigating the effects of GIC and government agencies for managing any potential consequences from GIC impact to critical infrastructure. Applications can be considered the ultimate goal of our GIC work. In assessing the status of the field, we quantify the readiness of various applications in the mitigation context. We use the Applications Readiness Level (ARL) concept to carry out the quantification. Key Points: We provide a broad overview of the status of the GIC field We utilize the Applications Readiness Levels (ARL) concept to quantify the maturity of our GIC‐related modeling and applications This paper is the high‐level report of the NASA Living With a Star GIC Working Group findings